2019
DOI: 10.2147/ott.s201473
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dosimetric comparison of different algorithms in stereotactic body radiation therapy (SBRT) plan for non-small cell lung cancer (NSCLC)</p>

Abstract: Purposes The main aim of the study was to investigate the dosimetric difference between acuros XB algorithm (AXB), anisotropic analytic algorithm (AAA), and pencil beam convolution (PBC) algorithm in stereotactic body radiation therapy (SBRT) plan for non-small cell lung cancer (NSCLC). Patients and Methods Thirty-eight NSCLC patients were included. GTV, PTV, and organs at risk were delineated by the radiation oncologists. Three optimized SBRT plans for each patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 15 publications
1
11
3
Order By: Relevance
“…Regarding PTV coverage parameters, our results differed from those published in the literature. While we found a lower D 95 and no significant difference in D 98 when comparing AAA with AXB, it is widely reported that AAA overestimates these parameters and the minimum dose 7,9,[18][19][20][21][22][25][26][27]30 . The reason for this discrepancy is that while our plans were initially optimized for AXB and then recalculated, keeping identical beam parameters for AAA, most prior studies adopted the opposite method.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…Regarding PTV coverage parameters, our results differed from those published in the literature. While we found a lower D 95 and no significant difference in D 98 when comparing AAA with AXB, it is widely reported that AAA overestimates these parameters and the minimum dose 7,9,[18][19][20][21][22][25][26][27]30 . The reason for this discrepancy is that while our plans were initially optimized for AXB and then recalculated, keeping identical beam parameters for AAA, most prior studies adopted the opposite method.…”
Section: Discussioncontrasting
confidence: 75%
“…To our knowledge, ours is the largest study to date comparing AXB (Dm and Dw) and AAA in lung patients undergoing SBRT. Previous studies have included up to 37 patients 9,19,23,28 , or present results for Dm mode only 7,8,18,24,26,27 , and most report only PTV or lung-related dosevolume parameters 7,8,18,[20][21][22][23][24][25][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations